Nature of Humic Acids of Some Soils of Semi Arid Part of Rajasthan - Joshi, D C; Ghonsikar, C P (Annals of Arid Zone, 2016)
The nature of humic acids extracted from eight soil profiles of the semi arid region of Rajasthan were studied for chemical and functional group analysis and for optical density characteristics. Carbon, nitrogen, phosphorus and sulphur content of humic acid ranged from 50 to 69, 4 to 9, 0.12 to 0.38 and 0.12 to 1.09 per cent and total acidity, carboxyl group contents mostly varied from 2 to 6, 1 to 3 and 1 to 5 m.e./per cent of humic acid. Low optical density and less steep curve in the humic acids of Jaipur, Ganganagar and Banswara red profiles indicated more aliphatic part in their structure. Uniform pattern in carboxyl group and optical density curves in most of the profiles indicated that humic acids present in their horizons were characterized by similar structural pattern.